TH1/TH17 profiles in crohn's disease: a cross sectional single centre study in postoperative crohn's disease. (13th March 2011) - Murugananthan, A U; Bernardo, D; Tozer, P; Tee, C T; Mann, E; Hart, A L; Arebi, N; Knight, S C; Al-Hassi, H O
Abstract : Introduction: Th1 and Th17 pathways are implicated in Crohn's disease (CD). In operative resection samples healthy ileum shows high TGFβ levels in patients who develop recurrence, with TGFβ being a known activator of the Th17 response. Other studies in CD show a dominant Th1 cytokine profile, with high levels of IFNγ, which reduce Th17 response and augment Th1 response. The relationship of Th1/Th17 cytokine profiles in postoperative CD has not been examined. The authors aimed to study tissue Th1/Th17 cytokine secretion after in vitro biopsy culture in postoperative CD. Methods: Colonoscopy was undertaken in postoperative CD patients. Recurrence graded as no/minimal inflammation (Rutgeert Score (RS) ≥1) or progressive inflammation (RS≥2). Ileal biopsies were cultured overnight and cell free supernatants obtained. Supernatant cytokines (IL-2, IL-4, IL-10, IL-17 TNFα, INFg and IL-6) were assessed by flow cytometry using cytometric bead array (Becton Dickinson). Statistical analysis was via unpaired t tests. Results: Consecutive patients attending endoscopy (n=24, 9M/15F) were identified. Mean age 45.0 years and time from I to C resection was 5.8 years; 5 patients were smokers. Drugs were thiopurines 13, Infliximab 1 and nil 10. Endoscopic severity was i0 n=5, i1 n=6, i2 n=5, i3 n=3, i4 n=5. Mean cytokine concentrations from supernatants are shown in the table 1. Comparison between RS≥1 and ≥2 showed that pro-inflammatory cytokines IL-17a (p<0.02) and IFNγ (p<0.03) were significantly higher in RS i2-i4 neo terminal ileum as compared with those with RS i0-i1. The regulatory cytokine IL-10 was significantly higher in patients with RS≥1 (p<0.038). Conclusion: Cytokine profiles in those with RS≥2, show higher levels of IL-17a and IFNγ and reduced IL-10 compared to RS≥1. This profile supports a Th17 and Th1 mediated response as one of the early instigators of endoscopic progression in postoperative CD. The authors' observation is consistent with recent findings of a T cell subset able to produce cytokines involved in both Th1 and Th17 responses. Previous therapies directed at Th1 pathway, for example, anti-IL-12p40 antibody ustekinumab and anti-IFNγ Fontolizumab failed to show significant clinical benefit in CD. Given our findings targeting the Th17 response, for example, with anti-IL-23 antibodies and anti-IL-17 may deliver improved therapeutic outcome.